It's lonelier at the top [Careers]. - Patel, P.
Betty Shanahan remembers often being the only woman in a meeting room. Someone would curse and then immediately look at her and say, "Sorry, Betty." "They were doing it as a nice gesture," says Shanahan, now the executive director of the Society of Women Engineers, in Chicago. "But the subtle message is 'Oh, I can't swear because Betty's here.' " It's a trivial example, she admits, but add up enough incidents like this one and it says you don't belong.